Development of Higher-Order Thinking Skills Assessment for High School Economic Subject - Dahlan, Dadang (Universitas Negeri Semarang, 2021)
Along with adopting a new curriculum in schools, there has been a shift of approach in terms of assessment matter that requires an assessment to be more comprehensive. This study aims to identify the economics teachers' competency deficit in developing the instruments for measuring higher-order thinking skills. The research method is Research and Development; it is a method to generate certain products and test product effectiveness. The product is in the form of an instrument model. The participants are 45 economics teachers and 270 students. The result shows that teachers' competency in making questions that involve a higher cognitive level is still considered low. It is found that only 12% of the teachers' questions are at the range of cognitive level analyzing to level creating, while the rest 88% are at the range of cognitive level remembering to level applying. This finding reflects the teachers' competency deficit in drafting HOTS questions based on the higher-order thinking aspect. According to this finding, an instrument model was then developed to measure higher-order thinking skills (HOTS). The developed instrument models are in the form of both multiple-choice and essay tests